An XMM-Newton view of the X-ray flat radio-quiet quasar PG 1416-129 - Porquet, D; Reeves, J; Markowitz, A; Turner, T; Miller, L; Nandra, K (2006)
(abridged) The radio-quiet quasar PG1416-129 (z=0.129) exhibits atypical optical and X-ray properties. Between 1990 and 2000, in response to its optical continuum decrease, the ``classical'' broad component of Hbeta almost completely disappeared, with a factor of 10 decrease in the line flux. In the X-ray band, this object was observed by Ginga in 1988 to have the hardest quasar photon index, with Gamma=1.1+/-0.1. We present an XMM/EPIC observation of PG1416-129 performed in July 2004. We analyze the time-averaged pn spectrum of this quasar, as well as perform time-resolved spectroscopy. We find that during the present XMM observation, PG1416-129 still has a rather hard photon index, both in the soft and hard energy ranges, compared to radio-quiet quasars but compatible with the photon index value found for radio-loud quasars. This object also shows long-term luminosity variability over 16 years by a factor of three with a variation of photon index from ~1.2 to ~1.8. In the soft energy band (0.2-2keV), we found a very weak soft X-ray excess compared to other RQ quasars. The whole time averaged spectrum is fit very well either by X-ray ionized reflection from the accretion disk surface, by a warm absorber-emitter plus power-law, or by a smeared absorption/emission from a relativistic outflow. While no constant narrow FeK line at 6.4keV is observed, we find the possible presence of two non-simultaneous transient iron lines: a redshifted narrow iron line at about 5.5keV (96.4% confidence level according to multi-trial Monte-Carlo simulations) at the beginning of this observation and the appearance of a line at 6.3-6.4keV (99.1% c.l.) at the end of the observation. These variable lines could be generated by discrete hot-spots on the accretion disk surface.